Autophagy-independent effects of autophagy-related-5 (Atg5) on exosome production and metastasis - Huishan Guo; Remy Sadoul; Derrick Gibbings (Molecular & Cellular Oncology, 2018)
Autophagy-related-5 (Atg5) and Autophagy-related-16-Like-1 (Atg16L1) canonically participate in autophagy. Recent research demonstrates that apart from this, they also control production of extracellular vesicles called exosomes by regulating acidification of late endosomes. Atg5-mediated exosome production increased migration and metastasis of breast cancer cells suggesting exosomes may perform some functions ascribed to autophagy.